Peacekeeping: Canada's past, but not its present and future? - Carroll, Michael (My University, 2016)
For Canadians there has been a great mystique surrounding peacekeeping. The idea that Canada is--or perhaps more appropriately was--a peacekeeping nation par excellence resonates deeply. Yet, however good this myth has made Canadians feel about themselves and their international contributions, it has ultimately done a disservice, leading to unrealistic expectations about what Canada and the blue berets could accomplish on the world stage. Furthermore, Canada's involvement in United Nations peacekeeping operations has not been motivated solely by altruism, but rather has been based on eminently practical factors of national self-interest. There is much that the Canadian Armed Forces has to offer the world in terms of future peace and security operations, but it remains to be seen whether peacekeeping factors into this equation.
Keywords: Canadian foreign policy; United Nations; Lester Pearson; Stephen Harper; peacekeeping; national interest